1992
DOI: 10.1002/jmv.1890370104
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus infections among heterosexual men and women with multiple sexual partners

Abstract: A prospective study of 65 men and 111 women with multiple heterosexual partners was designed to assess the prevalence and potential risk factors of genital human papillomavirus (HPV) infections. In addition, the HPV reservoir in genital, rectal, and oral mucosa was examined. The specimens for the detection of HPV DNA were taken from different sites such as the urethra and coronal sulcus (men), cervix and labia minora (women), anus, rectum, tongue, and buccal mucosa (both men and women). Women underwent speculu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 42 publications
0
30
2
Order By: Relevance
“…Of these, 110 women and 48 men could be followed until January 1992. These patients were included in this study (for a further description of the cohort, see van Doornum et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 110 women and 48 men could be followed until January 1992. These patients were included in this study (for a further description of the cohort, see van Doornum et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…At each visit, specimens were taken for HPV DNA detection with the PCR assay, using type-specific primers for HPV-6/11, -16, -18 and -33 as described (van Doornum et al, 1992). Samples from the males were taken from the mouth, anus, rectum, coronal sulcus and urethra.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 The samples of the mouth were PCR-negative in all 30 patients of this study. In other studyes [22][23][24][25][26] that used the same technique, the positivity rate ranged from 0 to 50%. We concluded that the presence of genital HPV infection does not appear to be a predisposing factor for oral HPV infection.…”
Section: Discussionmentioning
confidence: 97%
“…21 Many researchers have studied oral and genital HPV to discover whether genital infection by this virus could lead to infection elsewhere, such as in the mouth. [22][23][24][25][26] Van Doornum et al 22 (1992) applied the PCR to study oral and genital HPV in 65 males and 111 females. Examination of the mouth consisted of unaided visual inspection and scrapes for further study.…”
Section: Introductionmentioning
confidence: 99%